2011
DOI: 10.1155/2011/596801
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Transplantation: Does Age Increase Morbidity?

Abstract: Introduction. Pancreas transplantation (PTx) is the only definitive intervention for type 1 diabetes. Medical advancements in diabetes care have led to an aging PTx candidate pool. We report our experience with patients ≥50 years of age undergoing PTx. Methods. We reviewed 136 consecutive PTx patients at our institution from 1996–2010; 17 were ≥50 years of age. We evaluated demographics, surgical complications, acute rejection (AR) rates, nonsurgical infections, and survival outcomes. Results. Demographic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…While there were no factors identified to predict risk of MI or kidney graft loss, donor age was identified as a potentially useful risk factor for pancreas graft loss. Donor age has been established in many single‐centre and national database analyses to be associated with poor pancreas graft survival and forms the most significant predictor in the Pancreas Donor Risk Index .…”
Section: Discussionmentioning
confidence: 99%
“…While there were no factors identified to predict risk of MI or kidney graft loss, donor age was identified as a potentially useful risk factor for pancreas graft loss. Donor age has been established in many single‐centre and national database analyses to be associated with poor pancreas graft survival and forms the most significant predictor in the Pancreas Donor Risk Index .…”
Section: Discussionmentioning
confidence: 99%
“…Recipient age may also be a risk factor for poor outcomes after SPKT and contribute to pancreas or kidney failure. In many studies, recipient age has not been found to be a risk factor for relaparotomy [8,28], technical complications [19,28] or length of stay [28], although two studies found higher rates of bleeding in patients 50 years of age or older [29,30]. Whereas the aforementioned studies have evaluated donor and recipient risk factors for graft loss separately, ours is the first report to stratify outcomes by age-matched groups and to test for an interaction between donor and recipient age following SPKT.…”
Section: Discussionmentioning
confidence: 88%
“…Other studies have shown a lower patient survival for older patients (45 years or older) undergoing pancreas transplantation [29,30]. The authors concluded that older patients with type 1 diabetes are feasible suitable candidates for pancreas transplantation [32]. The rejection rate is lower in older than in younger recipients [29], but those older than 50 years have an increased rate of postoperative complications that should be taken into account when the benefits and risks are assessed [31].…”
Section: Agementioning
confidence: 98%